2020
DOI: 10.1177/1098300720910133
|View full text |Cite
|
Sign up to set email alerts
|

Impact of CW-FIT on Student and Teacher Behavior in a Middle School

Abstract: Positive behavior interventions and supports (PBIS) improve student behavior. Yet, teachers may not receive adequate training to implement PBIS at the classroom level. This study evaluated class-wide function-related intervention teams (CW-FIT) as a classroom-level behavior management system to determine whether the behavior of middle school students would improve with teacher implementation of CW-FIT. A multiple-baseline across conditions design was used to evaluate changes in on-task behavior of adolescent s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…Further, teachers maintained high levels of implementation fidelity and consumers (i.e., teachers and students) viewed the intervention favorably. Speight et al (2020) found similar results when implementing CW-FIT in an ethnically and socioeconomically diverse middle school. On-task behavior and teacher praise showed improvement with CW-FIT.…”
Section: Class-wide Function-related Intervention Teamssupporting
confidence: 57%
See 2 more Smart Citations
“…Further, teachers maintained high levels of implementation fidelity and consumers (i.e., teachers and students) viewed the intervention favorably. Speight et al (2020) found similar results when implementing CW-FIT in an ethnically and socioeconomically diverse middle school. On-task behavior and teacher praise showed improvement with CW-FIT.…”
Section: Class-wide Function-related Intervention Teamssupporting
confidence: 57%
“…The utility of CW-FIT across elementary settings has been well-established in the literature base (Caldarella et al 2015;Kamps et al 2015;Wills et al 2018), and evidence is emerging for intervention efficacy in middle school classrooms (Caldarella et al 2019;Orr et al 2020;Speight et al 2020;Wills et al 2019). Though the results should be interpreted cautiously given the limitations, this study provides evidence CW-FIT may lead to similar improvements in high school student and high school teacher behavior.…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…More recently, class-wide function-related intervention teams (CW-FIT), a universal approach to classroom management originally developed for elementary schools, was modified and evaluated in middle school settings (Monson, Caldarella, Anderson, & Wills, 2020; Orr et al, 2020; Speight, Whitby, & Kucharczyk, 2020; Wills, Caldarella, Mason, Lappin, & Anderson, 2019). Several studies in various middle school settings suggest that CW-FIT improved student behaviors and increased their time-on-task.…”
Section: Gaps In the Literaturementioning
confidence: 99%
“…CW-FIT incorporates many research-based behavioral strategies such as: direct instruction of skills, self and peer management, extinction by removing reinforcement, differential reinforcement of alternative behaviors through dependent group contingencies, token economy, and teacher praise (University of Missouri, 2019). CW-FIT has been researched over 20 times (e.g., Jolstead, Caldarella, Hansen et al, 2017;Kamps, Wills, Dawson-Bannister et al, 2015;Speight, Whitby, & Kucharczyk, 2020). Recent studies investigated the use of the program in differing elementary schools and how the program affected student engagement, disruptive behaviors, and teacher praise.…”
Section: Intervention Programsmentioning
confidence: 99%